Chromium-histidinate ameliorates productivity in heat-stressed Japanese quails through reducing oxidative stress and inhibiting heat-shock protein expression - Akdemir, F.; Şahin, Nurhan.; Orhan, C.; Tuzcu, M.; Şahin, Kazım; Hayirli, A. (Taylor & Francis Ltd, 2015)
[Abstract Not Available]
Keywords: Nf-Kappa-B; Broiler-Chickens; Ascorbic-Acid; Methionine Supplementation; Transcription Factors; Growth-Performance; Serum Metabolites; Carcass Traits; Egg-Production; Meat Quality